Mucocelo esfenoidal: "Doença-camaleão" - Alzate Amaya, Fabian; Invêncio da Costa, Liliana; Padin Seara, Anselmo; Alvarez-Buylla, Mercedes (Revista Portuguesa de Otorrinolaringologia-Cirurgia de Cabeça e Pescoço, 2019)
Paranasal Sinus Mucocele is an entity caused by the accumulation of mucinous content in a pseudoencapsulated form at the level of paranasal sinuses. Its clinical presentation is variable, can produce intracranial and/or vascular compromise but it can also be discovered as a casual finding. Diagnosis is based on clinical suspicion and imaging tests, to identify the nature of the lesion. The treatment of choice is the endoscopic drainage to avoid future recurrences. In this article we present three cases of patients diagnosed with mucocele with different clinical manifestations that, thanks to a suspected diagnosis, therapeutic management was performed promptly, avoiding complications and recurrences on follow-up.